The Influence of Employer Attractiveness and Job Characteristics on Intention to Apply Among Generation Z Jobseekers in East Java: Organizational Reputation as a Mediating Variable (A Survey of LinkedIn Users): The Influence of Employer Attractiveness and Job Characteristics on Intention to Apply Among Generation Z Jobseekers in East Java: Organizational Reputation as a Mediating Variable (A Survey of LinkedIn Users) - Erlisa Viviantika Putri; Dewie Tri Wijayati Wardoyo; Anang Kistyanto (LP2M IAIN Palopo, 2026)
Purpose: This study aims to examine the influence of Employer Attractiveness and Job Characteristics on Intention to Apply among Generation Z jobseekers in East Java, Indonesia, with Organizational Reputation as a mediating variable. The research tests seven hypotheses to understand both direct and indirect effects of these variables on job application intentions. Methods: A quantitative survey approach was employed, targeting 100 Generation Z individuals with active LinkedIn accounts. Data were collected using structured questionnaires adapted from previous studies. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data, including measurement model evaluation (outer loading, AVE, reliability), structural model assessment (path coefficients, R²), and bootstrapping procedures for hypothesis testing. Results: The findings indicate that Employer Attractiveness directly and positively influences Intention to Apply, while Job Characteristics has no direct effect. Both variables significantly influence Intention to Apply indirectly through Organizational Reputation. Organizational Reputation also directly and positively affects Intention to Apply. The measurement and structural models demonstrated adequate validity, reliability, and goodness of fit. Implications: The study highlights the importance of employer branding, organizational reputation, and meaningful job design in attracting Generation Z talent. Organizations can leverage these insights to improve recruitment strategies and strengthen their reputation among young professionals. Future research is encouraged to explore other mediating factors and test the model in different regions or industries.